Intensi Vaksinasi Ditinjau dari Theory of Planned Behavior pada Masyarakat - Poerwanto, Agus; Marini, M (SAFE-Network, 2024)
Implementing COVID-19 vaccination is an important effort to prevent COVID-19 disease. COVID-19 vaccination specifically aims to reduce transmission or transmission of COVID-19, reduce morbidity and death rates due to COVID-19, achieve herd immunity in society and protect society so that it remains economically and socially productive. The success of vaccination implementation is determined by the high desire of the public to get the COVID-19 vaccination. According to the Theory of Planned Behavior (TPB), it is said that a person will carry out a behavior if he has a strong intention/desire to do it. The aim of this research is to determine the intention to participate in the COVID-19 vaccination in terms of the Theory of Behavior in the people of Karangtengah hamlet, Pasuruan district. It is hoped that this research can contribute information related to social influences on the apathy of village communities regarding administering the Covid-19 vaccine. This research is expected to help the village government to create positive social learning that can make village communities aware of the importance of the Covid-19 vaccine. This research is quantitative research. using a correlational design. This research involves two types of variables, namely independent variables and dependent variables. The research variables used in this research are Theory of Planned Behavior (Attitudes, Norms, Behavioral Control) as the Independent Variable (X) and Intention as the Dependent Variable (Y). The data collection technique in this research is by using a questionnaire. The questionnaire used is a Likert scale form. The Likert scale is used to measure the attitudes, opinions and perceptions of a person or group of people about social phenomena. The variables to be measured are described into variable indicators on a Likert Scale.